Distribution Network Planning Using a Constructive Heuristic Algorithm - Lavorato, Marina; Rider, Marcos J.; Garcia, Ariovaldo V.; Romero, Ruben [UNESP]; IEEE (Ieee, 2009)
An optimization technique to solve distribution network planning (DNP) problem is presented. This is a very complex mixed binary nonlinear programming problem. A constructive heuristic algorithm (CHA) aimed at obtaining an excellent quality solution for this problem is presented. In each step of the CHA, a sensitivity index is used to add a circuit or a substation to the distribution network. This sensitivity index is obtained solving the DNP problem considering the numbers of circuits and substations to be added as continuous variables (relaxed problem). The relaxed problem is a large and complex nonlinear programming and was solved through an efficient nonlinear optimization solver. A local improvement phase and a branching technique were implemented in the CHA. Results of two tests using a distribution network are presented in the paper in order to show the ability of the proposed algorithm.
Keywords: Distribution network planning; constructive heuristic algorithm; mixed binary nonlinear programming; power systems optimization; KNITRO; AMPL